Movie makes magic! Keynote address: The value of History as a school subject in an age of science And technology (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
In this article the focus is on the value of History for a society dominated by the natural sciences and technology. This domination may lead to the questioning of the value of a subject like History where the demand is for “bread and butter” subjects which will enable learners to gain financially from the world of work. Against this background, questions such as the following arise: Is there still a place for the social sciences? If the answer is yes, what is the possible value of History in a society driven by financial forces and technological developments? Can technology be utilised to convey the importance of History? What is the possible contribution of technology towards the enhancement of the value of History and acquiring a sound historical and critical understanding of both the past and the present?
Keywords: value of History; social sciences; technology; importance of History; critical understanding